PENGARUH KEADILAN ORGANISASIONAL TERHADAP PERILAKU KERJA KONTRA PRODUKTIF DAN DAMPAKNYA PADA KEPUASAN KERJA PEGAWAI DINAS SOSIAL PROVINSI KALIMANTAN BARAT - iryansyah iryansyah (Universitas Tanjungpura, 2020)
This research was conducted with the aim of testing and analyzing the effect of organizational justice on counterproductive work behavior and its impact on job satisfaction of West Kalimantan Provincial Social Service Employees. This type of research is a survey using a quantitative approach. The population in this study were all ASN at the Social Service of West Kalimantan Province, amounting to 85 people. The research data were processed and analyzed using the path analysis model (SPSS 18). Based on the hypothesis testing it was concluded that distributive justice and interactional justice had a negative and not significant effect on counterproductive work behavior, while procedural justice had a negative and significant effect on counterproductive work behavior. The results of hypothesis testing further indicate that distributive justice, procedural justice, and interactional justice have positive and significant effects on job satisfaction, while counterproductive work behavior has a negative and significant effect on job satisfaction.Keyword : Distributive justice, procedural justice,interactional justice, counterproductive work behavior and job satisfaction